The Insights of Microbes' Roles in Wound Healing: A Comprehensive Review - Thambirajoo Maheswary; Asma Abdullah Nurul; Mh Busra Fauzi (MDPI AG, 2021)
A diverse range of normal flora populates the human skin and numbers are relatively different between individuals and parts of the skin. Humans and normal flora have formed a symbiotic relationship over a period of time. With numerous disease processes, the interaction between the host and normal flora can be interrupted. Unlike normal wound healing, which is complex and crucial to sustaining the skin's physical barrier, chronic wounds, especially in diabetes, are wounds that fail to heal in a timely manner. The conditions become favorable for microbes to colonize and establish infections within the skin. These include secretions of various kinds of molecules, substances or even trigger the immune system to attack other cells required for wound healing. Additionally, the healing process can be slowed down by prolonging the inflammatory phase and delaying the wound repair process, which causes further destruction to the tissue. Antibiotics and wound dressings become the targeted therapy to treat chronic wounds. Though healing rates are improved, prolonged usage of these treatments could become ineffective or microbes may become resistant to the treatments. Considering all these factors, more studies are needed to comprehensively elucidate the role of human skin normal flora at the cellular and molecular level in a chronic injury. This article will review wound healing physiology and discuss the role of normal flora in the skin and chronic wounds.